Study on the On/Off Ratio of the Cylindrical Surrounding Gate CNT Transistor Using Nonequlibrium Greens Function Approach (Journal of Scientific Research, 2015)
The effects of the nanotube diameter, channel length, gate dielectric constant and gate dielectric thickness on the on-off current ratio performance of cylindrical surrounding gate carbon nanotube transistors are studied using a ?-orbital tight binding simulation model. The focus is both on Schottky-barrier and the doped source-drain contact devices. The on current significantly improves with high-? gate dielectric, whereas off current decreases. The device on-off current ratio improves, from 6.33 × 105 to 1.5 × 106 for doped contact and from 0.61 × 104 to 1.22 × 104 for SB device with thinner gate oxide. Minimum leakage current increases with larger diameter tube but on-current has no significant improvement. I-V characteristics are independent of channel length when it is larger than 15 nm. Significant increase in off-current occurs due to scaling the channel length down to 10 nm but on-off ratio still exceeds 103. In all cases, on-off ratio is higher and the effect of scaling is more prominent for doped contact devices than SB contact devices.